PERAN KELUARGA TERHADAP PENDIDIKAN ISLAMI DI PAUD QURRATUL A’YUN KAMPAR - Kusmiran, Kusmiran; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This research is to determine the role of the family in the perspective of Islamic education in PAUD Qurratul A'yun Kampar. This study uses a quantitative descriptive method. The results showed that: 1) Family understanding of religious education: 20 respondents, 80% stated that religious education at an early age was important, while 20% said it was not important, 2) parents graduated from junior high school as much as 10%, high school graduates as much as 25% , 55% of bachelor's graduates and 10% of master's graduates, and 3) Worship Education: 90% of parents teach prayers, memorizing short letters, reading iqra', 5% of parents call private teachers and the other 5% rely on education from schools .